William Plumer papers - Plumer, William, 1759-1850.
Correspondence; letterbooks; diaries; nine volumes of writings including his autobiography, notes on the proceedings of Congress, and transcriptions of essays, poetry, and extracts from various sources; and other papers relating to Plumer's political career, writings as an essayist, and personal affairs. Subjects include New Hampshire history, politics, courts, and state militia; New England politics; relations with the Barbary States, France, Great Britain, and Spain; the Louisiana Purchase; the purchase of Florida; and the Federalist Party (Federal Party). Other subjects include the Dartmouth College controversy, impeachment cases of judges Samuel Chase and John Pickering, agriculture, education, government, international trade, paper money and the public debt, politics, and religion. Family correspondents include Plumer's wife, Sarah Plumer; his son, William Plumer, Jr.; and his brother, Daniel Plumer. Other individuals represented by correspondence or subject matter include John Adams, John Quincy Adams, Aaron Burr, Henry Clay, Charles Cutts, John Farmer, John Taylor Gilman, Salma Hale, John Adams Harper, Isaac Hill, Thomas Jefferson, John Langdon, Arthur Livermore, Edward St. Loe Livermore, Jeremiah Mason, Jacob Bailey Moore, Nahum Parker, James Sheafe, Jeremiah Smith, and Levi Woodbury.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
U.S. senator from New Hampshire, governor and state legislator of New Hampshire, essayist, and historian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John, -- 1735-1826.; Adams, John Quincy, -- 1767-1848.; Burr, Aaron, -- 1756-1836.; Chase, Samuel, -- 1741-1811 -- Impeachment; Clay, Henry, -- 1777-1852.; Cutts, Charles, -- 1769-1846.; Farmer, John, -- 1789-1838.; Gilman, John Taylor, -- 1753-1828.; Hale, Salma, -- 1787-1866.; Harper, John Adams, -- 1779-1816.; Hill, Isaac, -- 1789-1851.; Jefferson, Thomas, -- 1743-1826.; Langdon, John, -- 1741-1819.; Livermore, Arthur, -- 1766-1853.; Livermore, Edward St. Loe, -- 1762-1832.; Mason, Jeremiah, -- 1768-1848.; Moore, Jacob Bailey, -- 1797-1853.; Parker, Nahum, -- 1760-1839.; Pickering, John, -- 1737-1805 -- Impeachment; Plumer, Daniel, -- 1770-1852 -- Correspondence; Plumer, Sarah -- Correspondence; Plumer, William, -- 1789-1854 -- Correspondence; Sheafe, James, -- 1755-1829.; Smith, Jeremiah, -- 1759-1842.; Woodbury, Levi, -- 1789-1851.; New Hampshire. -- Militia; Spain. -- 1819 February 22.; United States. -- Congress; Dartmouth College; Federal Party (U.S.); Agriculture; Courts -- New Hampshire; Debts, Public -- United States; Education; International trade; Louisiana Purchase; Paper money -- United States; Political science; Politics, Practical; Religion; Trials (Impeachment) -- United States; Africa, North -- Foreign relations -- United States; Florida -- History -- Spanish colony, 1784-1821.; France -- Foreign relations -- United States; Great Britain -- Foreign relations -- United States; New England -- Politics and government; New Hampshire -- History; New Hampshire -- Politics and government -- 1775-1865.; Spain -- Foreign relations -- United States; United States -- Foreign relations -- Africa, North; United States -- Foreign relations -- France; United States -- Foreign relations -- Great Britain; United States -- Foreign relations -- Spain; United States -- Politics and government -- 1783-1865.; Essayists; Governors -- New Hampshire; Historians; Legislators -- New Hampshire; Senators, U.S. Congress -- New Hampshire